The genus Saitobryum (Pottiaceae) revisited. (2nd July 2016) - Cano, María J.; Jiménez, Juan A.
Abstract : The genus Saitobryum R.H.Zander comprises two species: S. lorentzii (Müll.Hal.) Ochyra distributed in Mexico and the Central Andes and Saitobryum pascoense M.J.Cano & J.A.Jiménez from the Central Andes of Peru, described here as new. The new species is distinguished from S. lorentzii by its upper and middle laminal cells papillose throughout, border of 2–3 rows of thick-walled and smooth cells, lamina usually with bistratose patches, and occasionally bistratose margins. The diagnostic characters of Saitobryum are re-evaluated and a key to the species of this genus is provided. Both species are described and illustrated. New localities for S. lorentzii and a map showing the complete distribution of this genus are given.